2018
DOI: 10.1021/acs.iecr.8b04616
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Enzymatic Oxidation of Xenobiotics by Hydrogen Peroxide through Oxidation–Reduction Potential Measurements

Abstract: In this work, three xenobiotics (orange II, phenol, and bisphenol A) were oxidized by hydrogen peroxide in the presence of a horseradish peroxidase (HRP) using a fed-batch system. During the experiments, the oxidation− reduction potential (ORP) of the reaction mixture was measured continuously. Results demonstrate that ORP values only increased when both substrates of the enzyme (hydrogen peroxide and the target compound) were present in the reaction mixture. For all of the tested pollutants, the continuous ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 32 publications
(49 reference statements)
1
22
0
Order By: Relevance
“…While decolorization assays without P evaluate the adsorption of OII onto the different tested electrospun matrices, decolorization under the presence of P reflected both adsorption and oxidation processes. According to a previous work, 8 the optimum pH value to maximize the peroxidase activity of the tested HRP ranged between 9 and 10. Thus, adsorption tests were performed by immersing M, MA, or MAH membranes (1.0 ± 0.1 cm 2 ) in 4.4 ml of PB solution (100 mM, pH 9.0) containing OII (0.045 mM).…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…While decolorization assays without P evaluate the adsorption of OII onto the different tested electrospun matrices, decolorization under the presence of P reflected both adsorption and oxidation processes. According to a previous work, 8 the optimum pH value to maximize the peroxidase activity of the tested HRP ranged between 9 and 10. Thus, adsorption tests were performed by immersing M, MA, or MAH membranes (1.0 ± 0.1 cm 2 ) in 4.4 ml of PB solution (100 mM, pH 9.0) containing OII (0.045 mM).…”
Section: Methodsmentioning
confidence: 97%
“…In a previous work, Morales Urrea et al 8 demonstrated that the oxidation of OII by hydrogen peroxide catalyzed by HRP produced an oxidation product (OP) that contributes to the absorbance of the reaction mixture. Because these OII oxidation products (OP) cannot be further oxidized by HRP under the tested conditions, the absorbance of the reaction mixture at a given time t ( A t ) is the contribution of OII ( A OII ), and OP ( A OP ) 8 : At=AOII+AOP Taking into account that 1 mol of OII yields 1 mol of OP, 8 and assuming that the absorbance at the end of the experiment (A f ) is only due to the presence of OP (e.g., in the cases when the oxidation of OII is complete), the following expression can be obtained, AtA0=fOII+()1fOIIrf where A 0 is the initial absorbance of the reaction mixture, fOII is the ratio between the OII concentration at time t and the initial OII concentration, and rf is the ratio between final ( A f ) and initial ( A 0 ) absorbances. According to this definition, ()1rf represents the maximum decolorization degree that can be achieved under the excess of oxidant when the oxidation of OII is complete.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations